Politik Tubuh Perempuan Antara Kontrol Sosial dan Resistensi - Swastini, Ni Luh Manik Esa; Erviantono, Tedi; Noak, Piers Andreas (Socio-political Communication and Policy Review, 2025)
This article explores the politics of women's bodies within Indonesia's social, cultural, religious, and media contexts. Women's bodies are not merely biological entities but sites of power regulated by institutions such as the state, religion, tradition, and media. Using a literature review approach, this study reveals how women's bodies are subjected to moral and symbolic regulation, yet also serve as spaces of resistance and political expression. Women assert agency through social media, art, and reinterpretation of religious texts. The ecofeminist perspective further expands the analysis by linking the exploitation of women's bodies and nature under patriarchal capitalism. This article emphasizes the importance of recognizing women's bodies as active political subjects in the struggle for gender justice. Abstrak Artikel ini membahas politik tubuh perempuan dalam konteks sosial, budaya, agama, dan media di Indonesia. Tubuh perempuan tidak hanya dipahami sebagai entitas biologis, tetapi juga sebagai medan kekuasaan yang dikontrol oleh berbagai institusi seperti negara, agama, adat, dan media. Melalui pendekatan literature review, artikel ini mengungkap bagaimana tubuh perempuan menjadi objek regulasi moral dan simbolik, namun juga menjadi ruang resistensi dan ekspresi politik. Perempuan menunjukkan agensi melalui media sosial, seni, dan reinterpretasi teks keagamaan. Pendekatan ekofeminisme turut memperluas pemahaman dengan mengaitkan eksploitasi tubuh perempuan dan alam dalam sistem kapitalisme patriarkal. Artikel ini menegaskan pentingnya melihat tubuh perempuan sebagai subjek politik yang aktif dalam perjuangan menuju keadilan gender. Kata Kunci: politik tubuh, perempuan, kontrol sosial, resistensi, media, ekofeminisme